Morbidity and mortality in patients with cardiovascular risk factors and obstructive sleep apnoea: results from the DIAST-CHF cohort. (July 2019) - Haarmann, Helge; Koch, Jennifer; Bonsch, Nina; Mende, Meinhard; Werhahn, Stefanie Maria; Lüers, Claus; Stahrenberg, Raoul; Edelmann, Frank; Holzendorf, Volker; von Haehling, Stephan; Pieske, Burkert; Andreas, Stefan; et al.
Abstract: Study objectives: Aim of the study was to investigate the association between obstructive sleep apnoea (OSA) and cardiovascular morbidity and mortality in a cohort of patients with cardiovascular risk factors. Methods: In this prospective study, 378 patients of the DIAST-CHF cohort were screened for OSA by home polygraphy. Inclusion criteria were risk factors for diastolic heart failure, such as hypertension, diabetes mellitus, atherosclerotic disease, or history of chronic heart failure. Patients were followed up after 1, 2, 5, 9 and 10 years for the occurrence of major adverse cardiac and cerebrovascular events (MACE and MACCE). Results: 344 patients were included in the analysis, of which 60% were diagnosed with OSA (apnoea-hypopnoea index ≥5/h). Overall mortality was higher in the OSA group (14.9% vs. 5.9%; p = 0.007), but significance disappeared after adjustment for age and sex (hazard ratio (HR) 1.89, 95% confidence interval (CI) 0.86–4.16, p = 0.12). There was no significant difference in the occurrence of MACE or MACCE in patients with OSA compared to those without OSA (MACE: 31% vs. 30%; p = 0.61; MACCE: 32% vs. 30%; p = 0.53). Conclusion: We did not find evidence of an adverse effect of OSA on cardiovascular morbidity and mortality in a cohort of patients with cardiovascular risk factors. Highlights: Obstructive sleep apnoea is highly prevalent in patients with cardiovascular disease. No independent impact of obstructive sleep apnoea on mortality in 10-year follow-up. Obstructive sleep apnoea did not affect the occurrence of cardiovascular events.